2014
DOI: 10.1149/2.013403jss
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Characteristics of Eu3+-Doped Double-Perovskite Phosphors

Abstract: Eu 3+ -doped triple tellurium double perovskites LiBaLa [TeO 6 ], NaBaLa [TeO 6 ], LiBaBi [TeO 6 ] and NaCaBi [TeO 6 ] were synthesized by the general high temperature solid-state reaction. The crystal phase formations and morphology of the phosphates were confirmed by X-ray powder diffraction (XRD) and scanning electron microscope (SEM) measurements, respectively. The luminescence properties, including the photoluminescence (PL) excitation and emission spectra, decay curves (lifetimes), the color coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…For two-step Eu-BZO powders, the domination transition changed from 5 D0 → 7 F1 to 5 D0 → 7 F0 as the heating temperature increased from 1100 °C to 1400 °C; also, the emission changed from the reddish-orange color to orange, as Figure 6a-c show. [16]. Those results suggest that the different Eu 3+ ion transitions will happen.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…For two-step Eu-BZO powders, the domination transition changed from 5 D0 → 7 F1 to 5 D0 → 7 F0 as the heating temperature increased from 1100 °C to 1400 °C; also, the emission changed from the reddish-orange color to orange, as Figure 6a-c show. [16]. Those results suggest that the different Eu 3+ ion transitions will happen.…”
Section: Resultsmentioning
confidence: 81%
“…Those photographs prove that Eu-BZO phosphors with very bright emission intensity can easily be obtained by heating oxide precursors. Yu et al found that Eu 3+ -doped LiBaLaTeO6, NaBaLaTeO6, and LiBaBiTeO6 show the dominant transition of 5 D0 → 7 F2 with a pure red luminescence color and Eu 3+ -doped NaCaBiTeO6 presents the dominant reddish-orange emission from the transition of 5 D0 → 7 F1 [16]. Those results suggest that the different Eu 3+ ion transitions will happen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eu 3 þ shows red-luminescence (570À 750 nm) from the intra-configurational 4f 6 -4f 6 parity forbidden transitions with narrow peaks of 5 D 0 -7 F J (J ¼0-4) with lifetime in ms scale [3]. However, Eu 2 þ has broad emission from the parity allowed transitions 4f 6 5d 1 -4f 7 with fast decay (ns scale) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%